Effects of Chopping on Utilization of Sorghum Stover by Nubian Goats - Mohammed Hamed, Asma Himmed; Elimam, Mohamed Elamin (Pakistan Journal of Nutrition, 2009)
Effects of chopping sorghum stover (Tabat variety) on Dry Matter Intake (DMI), apparent digestibility and body weight changes in Nubian goats were studied in the Gezira, Sudan. The chemical composition of the stover (%) was 96.78 ±0.83, 1.43 ±0.02, 4.65 ±0.39, 42.98 ±0.01, 9.99 ±0.89 and 40.96 ±1.24 for DM, EE, CP, CF, ash and NFE, respectively. Dry matter intake on different basis was higher for the chopped stover and the effect was significant (p